Les Principes De Jogjakarta: Principes sur l'application de la législation internationale des droits humains en matière dórientation sexuelle et d'identité de genre (2006)
Principes additionnels et obligations additionnelles des états au sujet de l’application du droit international des droits humains en matière d’orientation sexuelle, d’identité de genre, d’expression de genre et de caractéristiques sexuelles pour completer les Principes de Jogjakarta Depuis leur adoption en 2006, les Principes de Jogjakarta ont évolué pour devenir une déclaration faisant autorité sur les droits humains des personnes « d’orientations sexuelles et d’identités de genre diverses ». La dernière décennie a été témoin de développements significatifs dans le domaine du droit international des droits humains, ainsi que dans la compréhension des violations des droits humains subies par les personnes « d’orientations sexuelles et d’identités de genre diverses », et dans la reconnaissance des violations souvent distinctes touchant des personnes en raison de leur « expression de genre » ou de leurs « caractéristiques sexuelles ».Les Principes de Jogjakarta plus 10 (PJ+10) visent à documenter et à détailler ces développements à travers un ensemble de Principes additionnels et d’Obligations additionnelles des États.
https://yogyakartaprinciples.org/principles-fr/
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; antiracisme; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; inégalités; outils; pol4022; premier cycle; périodes historiques; queer; racisme; régions géographiques; science politique; sud global; systèmes d'oppressions; thématiques

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." – Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Changer de sexe: identités transsexuelles - Augst-Merelle, Alexandra; Nicot, Stéphanie (Cavalier bleu, 2006)
Rédigé par deux transgenres, un portrait de la communauté transexuelle française qui fait justice des préjugés et s'efforce de balayer toutes les idées reçues.
Section: 187, [4] pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; militance; premier cycle; périodes historiques; queer; queer of color; régions géographiques; shm4000; systèmes d'oppressions; thématiques; transféminisme

Les conceptions de l’identité sexuelle, le postmodernisme et les textes littéraires - Boisclair, Isabelle; Saint-Martin, Lori (Recherches féministes, 2006)
Le présent article trace d’abord un bref portrait de trois conceptions dominantes de l’identité sexuelle : le modèle patriarcal, le modèle féministe et le modèle postmoderne. Puis, après avoir présenté plus longuement le dernier, il analyse deux romans relayant cette conception postmoderne de l’identité de sexe/genre, l’un écrit par un homme (Self, de Yann Martel, paru en 1996), et l’autre par une femme (Ce qu’il en reste, de Julie Hivon, paru en 1999). Dans ces deux romans, qui revêtent de ce fait une importante dimension politique, les identités figées sont mises à mal tant discursivement que formellement - par la déconstruction des signes du passé et la mise en place de dispositifs énonciatifs confondant hommes et femmes, par exemple. Ils participent ainsi à une conception culturaliste de l’identité sexuelle, selon laquelle le genre est une performance.,This article begins by briefly introducing three major frameworks for conceptualizing gender identity : a patriarchal model, a feminist model and a postmodern model. After exploring the third in greater depth, it offers a reading of two novels of postmodern gender identity, one by a male author (Self by Yann Martel, 1996), one by a female author (Ce qu’il en reste by Julie Hivon, 1999). Both novels, which are therefore strongly political, challenge the concept of predetermined gender identity on the levels both of discourse and of form, by deconstructing older concepts and by blurring gender lines. They are therefore grounded in a view of gender identity as cultural construction and performance.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; discipline; fem1000; premier cycle; périodes historiques; queer; québec; ressource en ligne; régions géographiques; études littéraires

Comment devient-on homo ou hétéro? - Clerget, Stéphane (JC Lattès, 2006)
Le pédopsychiatre présente les découvertes récentes de la psychanalyse, la neurobiologie, la génétique, l'histoire, la sociologie, etc., à propos de la construction de l'identité sexuelle et de la part d'inné et d'acquis dans la définition des préférences sexuelles.
Section: 428 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Anti-Essentialism and Intersectionality - Grillo, Tina (Theorizing feminisms a reader, 2006)
'What is oppression ?' 'What should be done about it ?' Organized around these questions, Theorizing feminisms : a reader provides an overview of theoritical feminist writing about the quest for gender justice. Incorporating both classic and cutting-edge material, the reader takes into account the full diversity of women, highlighting the effects of race, ethnicity, nationality, class, sexuality, and religion on women's experience. Theorizing feminisms is organized into four sections and includes fifty-four essays. The first section introduces several basic concepts commonly employed when thinking about sexism - oppression, social construction, essentialism, intersectionality, gender, race, and class - and also raises questions about the perspective and legitimacy of the theorist. The second section surveys three approaches that attempt to characterize in a general way the source of injustice toward women : humanist feminism ('the sameness approach'), gynocentric feminism ('the difference approach'), and dominance feminism. Offering an alternate perspective, the third section introduces two 'localizing' approaches, grounded in postmodernism and identity politics, respectively. Skeptical of theories that attempt to analyze social phenomena across history and culture, authors in this section challenge, rather than answer, the text's organizing questions. The final section explores the relationship of feminism theory to three liberatory projects - postcolonialism, neo-materialism, and queer theory - that do not characterize themselves as feminist, yet take gender as a significant category of analysis. Each section opens with an introduction and each essay is followed by helpful study questions. the majority of the essays are presented in their entirety. Theorizing feminisms underscores the strong connection between feminist theory and practice by including essays that illustrate important political inspirations or applications of each theoritical approach. It also presents versions of the same approach from various points in history, revealing feminist theory to be dynamic and evolving, rather than static. Ideal for interdisciplinary courses in feminist theory, this volume will also serve as an invaluable reference for current and future generations of theorists."
Section: 1 vol. (XIX-564 p.) ; 24 x 19 cm
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; essentialisme; intersectionnalité; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; thématiques; théorie féministe

Global Recognition of Human Rights for Lesbian, Gay, Bisexual, and Transgender People - Suzanne M. Marks (Health and Human Rights, 2006)
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; justice sociale; pol4022; premier cycle; périodes historiques; queer; régions géographiques; science politique; systèmes d'oppressions; thématiques; violences; états-unis